Analisis Keterlibatan Militer dalam Jabatan Sipil Tahun 2019 di Indonesia - Fathullah Syahrul; Muh. Abdi Goncing (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2020)
This article aims to identify how the military is involved in civil service. During the phase of political upheaval in Indonesia the involvement of military groups was never even absent. This article finds that the two positions between civilians and the military have their respective duties in carrying out the mandate of the state which should not interfere with each other, based on the findings of this article that it turns out that until 2019 the efforts of military groups to fill civilian positions still exist. In addition, it was found that the political agenda in 2019 became a phenomenon with the strengthening of the issue of the Military Dual Function as a result of the transformation of the Indonesian Armed Forces Dual Function (ABRI) which had long disappeared after the collapse of the new order, so discourses of military involvement in civilian positions were considered political and became part of politics. From the project representation of political interests